Stroke in the newborn. Clinical report and literature review - R. Jakuškienė; V. Joneliūnaitė; U. Jucevičiūtė (Neurologijos seminarai)
Background. Stroke in the newborn or perinatal stroke (PS) is an acute brain ischemia with the duration up to the first 28 days of life with neurological symptoms or without them. Therefore, the diagnostics in clinical practice can become tricky due to misleading expression of this clinical syndrome. Whilst rare (1 in 1600-4000 cases), PS has 6 times higher prevalence in newborns compared to older children. Consequently, slight neurological symptoms such as convulsions, changes or asymmetry in muscle tone, exaggeration, weakening or disappearance of primitive reflexes should be taken into account urgently. According to American Heart Association’s studies in 2019, two thirds of perinatal victims have neurological disability or delayed mental performance. Case report. In this article we present a clinical case of perinatal ischemic stroke and literature review. We analyze acute brain ischemia in a newborn which developed during the first 12-24 hours of life with severe neurological symptoms and involved the area of the right internal carotid artery. Apart from “fencing reflex” and feeding rejection, epilepsy was not marked in the history of PS onset. The doctors agreed on the diagnosis based on neurosonography and computed tomography results, and the decision of performing craniotomy was made due to the risk of hemorrhagic stroke. Conclusions. Diagnosing perinatal stroke is a crucial and difficult task for all pediatricians because of its poor clinical expression and the necessity of urgent actions in order to avoid long term outcomes. Hence, thorough neurological exam and neuroimaging is an essential point in early diagnostics. Clinical practice reveals that there are no common guidelines to diagnose and manage perinatal stroke as an extremely urgent pathology which has a significant impact on a child’s further mental development.